Exposure to 10 Hz Pulsed Magnetic Fields Do Not Induce Cellular Senescence in Human Fetal Lung Fibroblasts - Sun, Chuan; Huang, Zheng; Qin, Houbing; Zhang, Jing; Wang, Sanying; Xu, Xiaogang; Ying, Shibo; Mao, Genxiang (Frontiers in Public Health, 2021)
Rapid population aging has led to a global burden of late-life diseases. As the largest risk factor for a multitude of age-related diseases, aging is not only the result of genotype but also closely related to external factors. With the rapid expansion in the usage of electromagnetic fields (EMFs), the effect of EMFs on aging has also attracted attention. Cells are the basic unit of organs and body tissues, and cellular senescence plays an important role in the aging process. The effect of EMFs on cellular senescence has been investigated in a few studies, but the information is limited and the results are inconsistent; thus, further investigation is required. In this study, we investigated the effect of 10 Hz pulsed EMFs on cellular senescence in a 2BS cell line, isolated from human fetal lung fibroblasts, and found that intermittent (1 d on/1 d off) exposure to 10 Hz pulsed EMFs at 1.0 mT for 2 weeks induced DNA damage, but no other significant phenotype of cellular senescence in 2BS cells.